Studies on hydrazide-hydrazones derivatives as acetylcholinesterase inhibitors - KAYMAKÇIOĞLU, BEDİA (AVES PRESS LTD, 2015)
Objective: Fifteen hidrazide-hydrazone derivatives were synthesized and evaluated for their ability to inhibit acetylcholinesterase (AChE) using a modification of Ellman's spectrophotometric method. Methods: Anti-acetylcholinesterase activity was evaluated by using a modification of Ellman'sspectrophotometric method. The spectrophotometric method is based on the reaction of released thiocholine to give a coloured product with a chromogenic reagent 5,5-dithio-bis-(2-nitrobenzoic acid). Results: Among the tested compounds, 4-fluorobenzoic acid [(4-methoxyphenyl) methylene] hydrazide (6) and 2-[(fluorobenzoyl) hydrazono]-1,3-dihydro-indol-3-one (15), showed noteworthy anti-AChE activity when compared to standard drug donepezil (IC50=0.054 +/- 0.002 mu M). Conclusion: The anti-AChE activity screening indicated that among the tested compounds, 6 with p-methoxyphenyl substitution and 15 with1,3-dihydro- indol-3-one substitution represent the most active compounds. Based on the activity results, it appears that bulky groups on the hydrazide-hydrazone moiety have made good contribution to the anti-AChE activity.
Keywords: Hydrazide; hydrazone; anti-acetylcholinesterase